Balancing Technology and Empathy: Faculty Perceptions of Artificial Intelligence in University Counseling - Masoud, Mohieddin; Kasheem, Majdy; Barkah, Sami; Alsaeh, Fatima; Baroud, Najah; Albshkar, Hajer (Universitas Islam Bunga Bangsa Cirebon, 2025)
This study explores university faculty members’ perceptions of integrating Artificial Intelligence (AI) into educational counseling, focusing on awareness, perceived usefulness, ethical implications, and institutional readiness. Using a descriptive quantitative design, data were collected from 250 faculty members at the University of Zawia through a structured questionnaire encompassing seven thematic domains. Participants were selected using a stratified random sampling technique to ensure balanced representation in academic disciplines and ranks. The results revealed generally high levels of awareness and positive attitudes toward AI applications in counseling. Faculty participants recognized the potential of AI to enhance efficiency, data management, and accessibility of counseling services. However, they expressed strong ethical and privacy concerns, particularly regarding data protection, bias, and the potential erosion of the human empathy central to counseling practice. Respondents also emphasized the need for structured training programs and institutional investment to strengthen technological readiness. The findings indicate that while cognitive acceptance of AI is high, affective and ethical reservations persist, reflecting the cultural emphasis on interpersonal trust and human connection in Arab academic contexts. Overall, the study underscores the importance of balancing technological innovation with ethical accountability and human values. It concludes that successful AI integration in university counseling requires a comprehensive framework encompassing staff development, policy guidance, and ethical safeguards to ensure that digital transformation remains human-centered and contextually appropriate.